Immediately Postpartum Care among Nurses/Midwives in Rania City - Renas Mohammed Khdir; Sanaa Hassan Abdul-sahib (Hawler Medical University, 2018)
Background and Objective: The first hours after childbirth are considered risky for mother and newborn, with many deaths occurring during or immediately after childbirth. Quality of care provided to mother and newborn after birth is important for the prevention of postpartum complications as well as neonatal and maternal morbidity and mortality. This study aimed to determine the knowledge and practice of nurses-midwives regarding care immediately after birth and to explore the relationship between nurses/midwives' socio demographic characteristics with overall their level of knowledge and practice. Methods: A descriptive study was conducted with all nurses and midwives (N=22) who worked in delivery room of Maternity Teaching Hospital in Rania City, from July 15, 2016 to December 20, 2017. A questionnaire and a checklist was designed to capture quality of care immediately after birth. The data were collected through interview and observation. Frequency, percentage and chi-square test were used for analyzing the data. Results: The results of the study revealed that the overall nurses/midwives' knowledge and practice regarding immediately post-delivery was good. In addition, the study results showed that there was no significant relationship with socio-demographic characteristics of nurse/midwives with the quality of immediately postpartum care. Conclusion: The overall knowledge and practice of the nurses/midwives regarding some basic immediate postpartum care where acceptable. A comprehensive training courses regarding standard immediately postpartum care is recommended. Keywords: quality of care, nurses, midwives.